Interactive three-phase structure for table tennis performance analysis: Application to elite men`s singles matches - Yu, J.; Gao, P. (Journal of Human Kinetics, 2022)
The aim of the current study was twofold: (a) to construct an Interactive Three-Phase Structure for table tennis performance analysis and (b) to apply the proposed structure to the performance analysis of elite men`s singles matches. The current structure makes improvements over the former ones in the following aspects: more comprehensive performance variables consisting of bilateral actions covering the whole rally competing process, a better phase division method fitting to the real match situation and more focused analysis achieved by the designed critical phase. The analysis of 56 elite men`s singles matches (5507 rallies) was conducted using the proposed structure. The results demonstrated that performance variables of the rally competing process ceasing in Phase 2 (initial attack and counterattack phase) were decisive for the rally outcome of elite men`s singles matches. The proposed structure provides practitioners with a better model to enhance the effectiveness of table tennis performance analysis.